2023
DOI: 10.1007/s13158-022-00344-9
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Quality in Three Distinct Early Childhood Programs Using the Brief Early Childhood Quality Inventory (BEQI)

Abstract: Quality early childhood care and education (ECCE) is important for young children’s holistic healthy development. As ECCE scales, contextually relevant and feasible measurement is needed to inform policy and programs on strengths and areas for improvement. However, few measures have been designed for use across diverse contexts. Drawing on principles of mixed methods design, this study reports on a new approach to ECCE quality measurement: the Brief Early Childhood Quality Inventory. Using data from the USA, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Few studies exist on the relative efficiency of these various quality assurance systems, especially in Majority World countries. A recent look at monitoring systems in Sub-Saharan Africa, however, suggested that prioritizing improvement over punitive measures may be more desirable in contexts where access to ECE is already limited, as the latter may create further barriers for teachers and/or families to take part in these services [25].…”
Section: Developing An Ece Quality Monitoring Measurementioning
confidence: 99%
See 2 more Smart Citations
“…Few studies exist on the relative efficiency of these various quality assurance systems, especially in Majority World countries. A recent look at monitoring systems in Sub-Saharan Africa, however, suggested that prioritizing improvement over punitive measures may be more desirable in contexts where access to ECE is already limited, as the latter may create further barriers for teachers and/or families to take part in these services [25].…”
Section: Developing An Ece Quality Monitoring Measurementioning
confidence: 99%
“…Empirical work in Majority World countries has mostly used three observational tools: the Early Childhood Education Rating System (ECERS) [29], the Classroom Assessment Scoring System (CLASS) [30] and the MELE. While a handful of other measures exist (e.g., TIPPS [31] and BEQI [32]), these three tools are currently the dominant ones to measure ECE quality. ECERS and CLASS were developed in the United States and have been used extensively in Majority World countries in the last decade [12].…”
Section: Empirical Work On Measuring Ece Quality In Majority World Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings point to several important areas for future research and data collection to inform policy. Nationally representative data at the pre-primary stage are rare in LMICs (Raikes, Sayre, & Lima, 2021), and data are important pre-requisite to evidence-based efforts to address inequality. Longitudinal data on young children and the trajectory of their development in LMICs are also much needed to understand critical points for intervention.…”
Section: Areas For Future Researchmentioning
confidence: 99%